Factorise and solve x^2 + 3x - 4 = 0

To factorise this equation, we must find two numbers that add together to make and multiply to make -4. These numbers must be -3 and -1. We would then rewrite the equation as (x-3)(x-1)=0.

To solve this equation, we need to make either (x-3)=0 or (x-1)=0. This means that there are two solutions to this question.

x-3=0 and x-1=0

This means x=3 or x=1.

Answered by Dylan J. Maths tutor

9488 Views

See similar Maths GCSE tutors

Related Maths GCSE answers

All answers ▸

Harry drives from Exeter to London in 4 hours at an average speed of 70km/h. Ron drives from Exeter to London in 5 hours. (a) Assuming Ron took the same route as Harry, calculate Ron's average speed.


Find the nth term of the sequence 7,11,15,19...


Simplify (8x^2 + 36x)/(2x + 9) and explain why it is an even expression.


What is the difference between the median and the mean values for this set of data: 11, 9, 21, 6, 18, 2, 17, 8, 7.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences